2011
DOI: 10.1007/s00404-011-1935-5
|View full text |Cite
|
Sign up to set email alerts
|

Uterine packing during cesarean section in the management of intractable hemorrhage in central placenta previa

Abstract: Uterine packing is a safe and effective technique in the control of intractable hemorrhage in cesarean section. It is a reasonable alternative to further surgical intervention in patients with intractable obstetric hemorrhage, especially in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Five took place in North America [2832], three in Asia [6, 33, 34], two in Europe [35, 36], and one in Australia [37] (Table 1). The articles were published between 2000 and 2016, and the final sample comprised 5146 unique pregnant women with placenta previa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five took place in North America [2832], three in Asia [6, 33, 34], two in Europe [35, 36], and one in Australia [37] (Table 1). The articles were published between 2000 and 2016, and the final sample comprised 5146 unique pregnant women with placenta previa.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of PPH ranged from 3.6% [31] to 58.7% [30]. When evaluated by STROBE quality assessment criteria, two studies [33, 37] received 9 points, five [2931, 34, 35] received 8 points, and four [6, 28, 32, 36] received 7 points (S2 Table). The quality scores showed that studies were acceptable quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57Y59 Hysterectomy may be required in cases of refractory hemorrhage. Al-Harbi et al 60 and Ge et al 61 reported the safety and effectiveness of uterine packing with sterile gauze in control of intractable hemorrhage during cesarean delivery for placenta previa especially in developing countries. Law et al 62 described the topical application of hemostatic gel to provide effective hemostatic control in the LUS at the time of laparotomy for postpartum hemorrhage after cesarean delivery for placenta previa.…”
Section: Antepartum Managementmentioning
confidence: 99%
“…At a glance, it seems there is little chance for uterine gauze packing to play a role in this field. But recently, the merits of uterine gauze packing have been reconsidered . Gauze packing is thus still a useful hemostatic technique in obstetric practice.…”
Section: Discussionmentioning
confidence: 99%